Rancang Bangun Robot Pembersih Panel Surya Menggunakan Metode Dry Cleaning Berbasis Fuzzy Logic Controller - Cahyanti, Veni; Muflih Rahman, Muhammad; Sulistyo, Eko; Dwisaputra, Indra (Jurnal Inovasi Teknologi Terapan, 2025)
Indonesia has great solar energy potential, but the efficiency of solar panels often decreases due to the accumulation of dust and dirt. This study develops a solar panel cleaning robot with a dry cleaning method based on a fuzzy logic controller. This robot is designed to clean panels automatically without using water or chemicals, using an ESP32 microcontroller and a TCS3200 color sensor, the robot will automatically work with the time set in the system. Tests were carried out on solar panels in dusty and non-dusty conditions. The results showed that the efficiency of solar panels in non-dusty conditions reached 36.17%, while in dusty conditions it dropped to 21.27%. These results emphasize the need for routine cleaning to maintain optimal solar panel performance. The fuzzy logic system on the robot will adjust the cleaning intensity based on the level of dust detected, thus making a significant contribution to maintaining solar panel efficiency. This study offers an environmentally friendly solution and can reduce operational costs related to cleaning solar panels and support the development of more sustainable renewable energy.